2014
DOI: 10.1111/head.12297
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Headache: Part II – Potential Mechanism and Treatment Considerations

Abstract: Obesity and headache are both associated with a substantial personal and societal impact, and epidemiologic studies have consistently identified a positive association between obesity and headache in general, as well as obesity and migraine specifically (see part I). In the current manuscript, we will discuss the potential mechanisms for the migraine–obesity association, with a focus on the central and peripheral pathophysiological pathways which overlap between migraine and those modulating the drive to feed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 88 publications
1
65
0
1
Order By: Relevance
“…Limited data in uncontrolled studies suggest that morbidly obese episodic and chronic migraineurs who undergo bariatric surgery have a reduction in monthly frequency and headache severity 3 to 6 months after surgery. [32][33][34][35] In addition, although several well-designed aerobic exercise trials have demonstrated efficacy for reducing headache days and pain severity in those with migraine, it remains unclear as to whether this is related to the exercise itself or as a result of weight loss. 32 We also found that being underweight (BMI , 18.5) was associated with a small increased risk of migraine.…”
Section: Neurology 88 May 9 2017 1801mentioning
confidence: 99%
See 2 more Smart Citations
“…Limited data in uncontrolled studies suggest that morbidly obese episodic and chronic migraineurs who undergo bariatric surgery have a reduction in monthly frequency and headache severity 3 to 6 months after surgery. [32][33][34][35] In addition, although several well-designed aerobic exercise trials have demonstrated efficacy for reducing headache days and pain severity in those with migraine, it remains unclear as to whether this is related to the exercise itself or as a result of weight loss. 32 We also found that being underweight (BMI , 18.5) was associated with a small increased risk of migraine.…”
Section: Neurology 88 May 9 2017 1801mentioning
confidence: 99%
“…[32][33][34][35] In addition, although several well-designed aerobic exercise trials have demonstrated efficacy for reducing headache days and pain severity in those with migraine, it remains unclear as to whether this is related to the exercise itself or as a result of weight loss. 32 We also found that being underweight (BMI , 18.5) was associated with a small increased risk of migraine. After adjusting for age and sex, the risk of migraine in underweight individuals was increased by 13% and remained significant after multivariate adjustments.…”
Section: Neurology 88 May 9 2017 1801mentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity may enhance the frequency and severity of headache attacks and appears to increase the risk for having migraine (1). Experimental results indicate multiple areas of overlap between migraine pathophysiology and the mechanisms related to excess body fat (2,3). Adipose tissue has significant endocrine functions by producing bioactive molecules that serve as regulators of metabolism and also possess immunoregulatory functions (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Studies evaluating interictal LEP levels in migraineurs have been inconclusive. [8][9][10][11][12] No previous studies have evaluated ictal LEP or resistin levels in migraineurs. …”
mentioning
confidence: 99%